"I am terrified of something happening to me" The lived experience of people with obesity during the COVID‐19 pandemic. Issue 6 (4th September 2020) - Grannell, Andrew; le Roux, Carel W.; McGillicuddy, Deirdre
Summary: Obesity is emerging as a risk factor for COVID‐19 disease severity. The impact of the pandemic and knowledge of obesity as a risk factor on the lived experience of people with obesity is not fully understood. The aim of this study was to investigate the impact of the COVID‐19 pandemic on people living with severe obesity (BMI ≥35 kg/m 2 ), currently engaged in multi‐modal treatment. The primary objectives were to examine the impact of the pandemic on their lived experience from a treatment and psychosocial standpoint and additionally explore their awareness of obesity as a risk factor for COVID‐19 disease severity. An in‐depth qualitative study was adopted employing semi‐structured interviews with open‐ended questions. Interpretive thematic analysis was adopted to analyse the data and identify key themes taking a grounded approach. Themes that emerged from the perspective of impact on lived experience were (a) challenge sustaining treatment and (b) psychosocial impact. There was an even split regarding awareness and lack of awareness of obesity as risk factor which itself contributes towards a negative psychosocial impact in most patients. The COVID‐19 pandemic is posing a diverse challenge to people with obesity. This has implications for their on‐going treatment. From an ethical standpoint, there is a need to fully elucidate the link between obesity and COVID‐19, disseminate this information using people friendly language and imagery in a manner that does not exacerbate a harmful psychosocial response or lead to stigmatization.